Architecture Design for Soft Errors - Mukherjee, Shubu (Elsevier, 2008)
This book provides practitioners, researchers, developers and students with a comprehensive description of the architectural techniques to tackle the soft error problem. It covers the new methodologies for quantitative analysis of soft errors as well as novel, cost-effective architectural techniques to mitigate them. To provide readers with a better grasp of the broader problem definition and solution space, this book also delves into the physics of soft errors and reviews current circuit and software mitigation techniques.